Internationalization of Consumer Law: A Game Changer, Hans W. Micklitz and Mateja Durovic, Springer Nature Switzerland, 2017, 89 pages, ISBN 978-3-319-45312-5 - Amrullah, Rizqi Baktiara (Faculty of Law, Universitas Negeri Semarang, 2019)
The book is titled Internationalization of Consumer Law: A Game Changer Written by Hans W. Miclitz and Mateja Durovic published by Springer in 2017. The book mainly talks about how consumer law has been applied in most countries with their own different standards. It also talks about the problems that arose from the laws that has been applied but it doesn’t provide solutions. The research conducted for this book only investigates how wide the application of consumer law is in the world. There are in total of 89 pages in this book divided into 6 chapters.